PENDAMPINGAN PESERTA DIDIK DI SDIT RAUDHAH AGAM UNTUK MENINGKATKAN HAFALAN JUZ 30 DENGAN METODE 3T + 1M - Pela Safni; Martin Kustati; Gusmirawati Gusmirawati (LPPM Universitas Bina Bangsa, 2023)
Learning to recite the Alquran and saying prayers is an advantage that students at SDIT Raudhah Agam have. The majority of them are able to read the Alquran fluently, memorize Juz 30, and memorize several selected prayers and hadiths. However, there are still several problems faced by the majority of students when doing muroja'ah, such as forgetting easily or memorizing things that don't stick in their memory for long, as well as a lack of accuracy in recitation when repeating memorization. Therefore, mentoring activities in memorizing the Alquran using the 3T + 1M method (Talqin, Tafahhum, Tikrar, and Muroja'ah) are considered as a solution to overcome this problem at SDIT Raudhah Agam. This method aims to help students optimize their potential, improve the quality of memorization, especially in the correct pronunciation of makhorijul letters and application of recitation, as well as strengthening memorization and understanding using the 3T + 1M method. An educational approach is used in this mentoring activity. The activity carried out at SDIT Raudhah Agam involved three students who had good abilities in memorizing the Alquran and reciting makhorijul letters, as well as applying the laws of tajwid correctly. Mentoring activities were carried out in 10 meetings in stages using the CBR method, namely the stages of identifying problems, exploring potential, setting goals, designing service methods, conducting training, and reflecting on the results. Evaluation of activities shows an increase in students' ability and quality of memorization and understanding of the Alquran in Juz 30